2020
DOI: 10.1111/cwe.12328
|View full text |Cite
|
Sign up to set email alerts
|

Does Outward Foreign Direct Investment Facilitate China's Export Upgrading?

Abstract: This paper empirically investigates the impact of China's outward foreign direct investment (OFDI) on its export sophistication. Using a provincial-level panel dataset and applying fixed effects and instrumental variable regression techniques, the study fi nds that, on average, OFDI has no signifi cant impact on China's export sophistication. However, after the full sample is divided into different regions, the study fi nds that OFDI has a positive and signifi cant impact on export sophistication in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Depending on the logarithmic mean divisia index (LMDI) deconstruction method, the three components of overall electricity severity, wealth creation, as well as reduced fuel architecture are used to examine shifts in the amount of carbon pollution. Some scholars argue that structural changes have little impact on carbon concentration (Zhang and Chen 2020 ).…”
Section: Background To the Industrial Structure Upgrading Modelmentioning
confidence: 99%
“…Depending on the logarithmic mean divisia index (LMDI) deconstruction method, the three components of overall electricity severity, wealth creation, as well as reduced fuel architecture are used to examine shifts in the amount of carbon pollution. Some scholars argue that structural changes have little impact on carbon concentration (Zhang and Chen 2020 ).…”
Section: Background To the Industrial Structure Upgrading Modelmentioning
confidence: 99%
“…Based on the PPML estimation method, our paper examines the impact of inclusive finance and environmental regulation on public health in 30 provinces except Tibet in 2006-2016 in China. The benchmark model is constructed as following the control variables in previous papers [see, e.g., (22)]:…”
Section: Empirical Model and Variable Selection Model Settingmentioning
confidence: 99%
“…Zhu et al [10], Li et al [11], and Li et al [12] identified a positive effect of FDI on manufacturing export sophistication, which comes from the export share of foreign-invested enterprises (FIEs) and the privately owned enterprises (POEs). Zhang and Chen [13] pointed out that outward foreign direct investment (OFDI) only had a positive impact on export sophistication in the developed coastal region. However, there may exist a nonlinear effect from FDI on export sophistication exhibiting diminishing returns [14,15].…”
Section: Literature Reviewmentioning
confidence: 99%